HUMAN RIGHTS-BASED LEGAL PROTECTION FOR HEALTH WORKERS IN CONFLICT ZONES - Maria Lusyana Br Ginting (Indonesian Journal of Health Administration (Jurnal Administrasi Kesehatan Indonesia), 2023)
Background: One of the human rights issues in the health sector is legal protection in conflict areas. The obstacles faced were the limited number of security personnel on guard and the long distance between the security post's location and the conflict's location. Aims: This study aims to determine how legal protection for health workers in conflict areas is. Methods: The method of this study is a literature review. The nature of this study is descriptive. The data collection method used is the literature study method, namely by collecting secondary data related to the issues raised. Results: The results of this study show that the central and regional governments have not been maximal in protecting health workers in conflict areas. Conclusion: Based on the results and discussion of this study, the recommendations are to make a grand design for health, security, and occupational safety for health workers, specifically in conflict areas, and to make standard operating procedures for handling cases of attacks on health workers in conflict areas. Keywords: Human Rights, Legal Protection. Health Workers.